ТАДБИРКОРЛИК ФАОЛИЯТИДА ШАХСЛАРАРО МУНОСАБАТЛАР МАСЪУЛИЯТИНИНГ ИЖТИМОИЙ ПСИХОЛОГИК ХУСУСИЯТЛАРИ - Халимова, М.В. (SCIENCE and SOCIETY, 2021)
The article presents a scientific and practical analysis to identify socio-psychological factors that develop the responsibility of interpersonal relations among entrepreneurs and improve the formation of relations of responsibility.